2012
DOI: 10.1007/s12529-012-9223-8
|View full text |Cite
|
Sign up to set email alerts
|

Type D Personality is Not Associated with Coronary Heart Disease Risk in a North American Sample of Retirement-aged Adults

Abstract: Neither Type D nor its constituent NA and SI traits were associated with absolute incident CHD risk in retirement-aged adults free of reported CHD. Optimal analytic practices and attention to patient/provider interaction behavior will improve our understanding of the association between Type D personality traits and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…A high level of NA has been shown to contribute to depression among adolescent girls [37]. Previous studies have also shown that the NA subscale is the one most associated to negative clinical outcome [20,38]. However, although no significant interaction effects were found, the explained variance according to Nagelkerke’s R 2 increased dramatically in the interaction models compared to the analyses of the dichotomized Type D personality variable.…”
Section: Discussionmentioning
confidence: 94%
“…A high level of NA has been shown to contribute to depression among adolescent girls [37]. Previous studies have also shown that the NA subscale is the one most associated to negative clinical outcome [20,38]. However, although no significant interaction effects were found, the explained variance according to Nagelkerke’s R 2 increased dramatically in the interaction models compared to the analyses of the dichotomized Type D personality variable.…”
Section: Discussionmentioning
confidence: 94%
“…risk of first coronary event in individuals without clinically established coronary disease; Larson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Type D personality has also been studied regarding the risk of CHD in populations without clinically established CHD [25]. Findings across studies are inconsistent, as several studies have failed to find any associations between Type D personality and cardiovascular outcomes [26], and provided ambiguous evidence regarding whether Type D personality can predict CHD. Denollet et al made the assumption that Type D personality is a significant predictor of cardiovascular events after adjustment for depressive symptoms because of the fact that the subcomponents of Type D personality, negative affectivity and social inhibition, activate different brain parts and result in different cortisol responses after exposure to social threats [27].…”
Section: Discussionmentioning
confidence: 99%